Isolation, characterization and evaluation of antioxidant activities of secondary metabolites producing actinomycetes of terrestrial origin - Padma B., Jessy; K., Saraswathi; P., Arumugam; Shiny R., Anna (International Journal of Research in Medical Sciences, 2018)
Background: Microbial secondary metabolites are important sources of natural compounds when compared to others with potential, beneficial therapeutic applications. There are chances of discovery of new Streptomyces species and new compounds from the respective genus. Due to ever and over increasing resistance of pathogenic bacteria to our current arsenal of antibiotics, a great need exists for the isolation and discovery of new antibiotics and other drug agents. Based on the above concept actinomycetes are mainly targeted for secondary metabolites production and evaluation of compounds therapeutically. Methods: Totally 15 pure isolates were obtained from two different soil samples by spread plate and quadrant streak techniques. Their colony and surface morphology were studied by morphological and biochemical characterization. Secondary metabolites were extracted by solvent extraction and the presence of bioactive compounds was detected by thin layer chromatography. The antioxidant potential was determined by Dot plot, DPPH and Phosphomolybdenum assay. The nature and the number of active compounds were identified by GC-MS analysis. Results: Among the 15 isolates, 10 isolates were found to have characteristic features of actinomycetes and 8 isolates were found to be fast growing actinomycetes. Among these 8 isolates, isolates of terrestrial origin were found to possess more bioactive compounds than those of marine origin and the four terrestrial isolates selected for evaluation of bioactive compounds and determination of antioxidant potential showed that the isolate TS 1010 had better and efficient secondary metabolite activity. Conclusions: Thus, from the above study it is seen that not only actinomycetes of marine origin, but terrestrial origin are also fast growers and possess better antioxidant and radical scavenging activity.